MCL1 inhibition enhances the therapeutic effect of MEK inhibitors in KRAS-mutant lung adenocarcinoma cells. (July 2019) - Tada, Makoto; Sumi, Toshiyuki; Tanaka, Yusuke; Hirai, Sachie; Yamaguchi, Miki; Miyajima, Masahiro; Niki, Toshiro; Takahashi, Hiroki; Watanabe, Atsushi; Sakuma, Yuji
Highlights: MCL1 knockdown alone does not induce apoptosis of KRAS -mutant lung cancer cells. MCL1-depleted KRAS -mutant lung cancer cells undergo apoptosis by MEK inhibition. Dual inhibition of MCL1 and Bcl-xL induces apoptosis of lung adenocarcinoma cells. Abstract: Objectives: MCL1 is an anti-apoptotic BCL2 family member that is highly expressed in various malignant tumors. However, little is known about the role of MCL1 in KRAS -mutant lung adenocarcinomas. In this study, we aimed to clarify whether MCL1 could be a therapeutic target in KRAS -mutant lung adenocarcinomas for which no effective molecular targeted drugs are available. Materials and methods: We examined to what extent MCL1 knockdown either alone or in combination with MEK inhibitor trametinib suppressed growth or induced apoptosis in the KRAS -mutant lung adenocarcinoma cell line H441 and EGFR -mutant lung adenocarcinoma cell line H1975. Furthermore, we investigated the therapeutic effects of dual inhibition of MCL1 and Bcl-xL, another anti-apoptotic BCL2 family member, in these two cell lines. Results: MCL1 knockdown alone did not induce apoptosis in H441 or H1975 cells. However, MCL1-depleted H441 and H1975 cells underwent apoptosis and decreased in number in the presence of trametinib. We also confirmed that combined therapy by MCL1 knockdown and trametinib almost completely suppressed the growth of H441 cells in vivo . Moreover, dual knockdown of MCL1 and Bcl-xL induced extensive apoptosis in H441 and H1975 cells. Conclusion: These findings suggest that combined treatments of MCL1 knockdown and trametinib or dual inhibition of MCL1 and Bcl-xL would be effective therapies for lung adenocarcinomas including the KRAS -mutant subtype.